Effect of Foreign Investment Flow, World Capital Market, Foreign Exchange and Country Risk to the Capital Market Return in Indonesia - Setiaji, Fajar; Wijayanto, Andhi (Universitas Negeri Semarang, 2019)
This study aims to determine the effect of foreign investment flow, World capital market (MSCI-World Index), rupiah exchange rate against US dollar and country risk (EMBI +) on Indonesia capital market return. The test is done by using multiple linear regression models. The test also uses stationery test data using Augmented Dicky Fuller Test (ADF) method. Then the Classic Assumption Test (Normality Test, Multicollinearity Test, Heteroscedasticity Test, and Autocorrelation Test), Hypothesis Testing includes Partial Test (t-test statistic), Goodness of Fit Test, and simulation test (statistic F test). The test result of this research by using multiple linear regression shows that the variable of foreign investment flows have a positive and significant effect on the return of Indonesian capital market, the variable risk country has no significant negative effect on the return of Indonesian capital market, while the world capital market variable and the rupiah exchange rate against US dollar significantly influence the return of Indonesia capital market.